Wzorce wychowania dzieci i młodzieży jako element integrujący kulturę życia rodzinnego polskiego ziemiaństwa w dobie zaborów - Bołdyrew, Aneta (Karkonoska Państwowa Szkoła Wyższa, 2011)
One of the most important tasks of a typical Polish gentry family by the end of the XIX-th century and at the beginning of the XX-th century was to hand down to younger generations patriotic values. To assure the continuity of the nation and to have the guarantee of the future freedom became sine qua non condition. It also became one of the main values of the gentry ethos. Gentry accepted the role of depositary of Polish nationality. The defeat of the November Uprising and the reprisals of the partitioning powers led to the radicalisation of attitudes, and of crucial importance became a principle to conflate the national cause with religion, which in tum led to crystallisation of the term „patriotic religion” whose upholder and priest became a woman - „Mother Pole”. Within the whole epoch the education of children was significant. In order to save them from the indoctrination they were taught national history, tradition and literature at home which stood in the opposition to the teaching officially practiced at school.
Keywords: children; youth; upbringing; gentry; family; Poland 19th century